2002
DOI: 10.1152/jn.00078.2002
|View full text |Cite
|
Sign up to set email alerts
|

Local Application of Dopamine Inhibits Pyramidal Tract Neuron Activity in the Rodent Motor Cortex

Abstract: Cortical neurons respond in a variety of ways to locally applied dopamine, perhaps because of the activation of different receptors within or among subpopulations of cells. This study was conducted to assess the effects of dopamine and the receptor subtypes that mediate the responses of a specific population of neurons, the pyramidal tract neurons (PTNs) in the rodent motor cortex. The specific subfamilies of dopamine receptors expressed by PTNs also were determined. PTNs were identified by antidromic stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 59 publications
1
41
0
Order By: Relevance
“…For example, the dopaminergic projection from the ventral tegmental area (Lindvall et al, 1974) terminates on pyramidal cells and interneurons (Sesack et al, 1995) and likely regulates their excitability. Studies in cats (Huda et al, 2001) and rodents (Awenowicz and Porter, 2002) have demonstrated reduced excitability in motor neurons, which produce the MEP to TMS, after application of DA. A recent study in monkey prefrontal cortex showed that DA decreases horizontal excitatory transmission in cortical layer 5 by a D1 receptormediated mechanism (Gao et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the dopaminergic projection from the ventral tegmental area (Lindvall et al, 1974) terminates on pyramidal cells and interneurons (Sesack et al, 1995) and likely regulates their excitability. Studies in cats (Huda et al, 2001) and rodents (Awenowicz and Porter, 2002) have demonstrated reduced excitability in motor neurons, which produce the MEP to TMS, after application of DA. A recent study in monkey prefrontal cortex showed that DA decreases horizontal excitatory transmission in cortical layer 5 by a D1 receptormediated mechanism (Gao et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…There, DA affects the activity of layer V motorneurons and the cortico-spinal tract (Awenowicz and Porter 2002;Vitrac et al 2014). Thus, besides supporting plasticity, dopaminergic projections to M1 are ideally suited to control the cortico-fugal output of the primary motor cortex.…”
Section: Functional Aspects Of the Dopaminergic Midbrain-m1 Projectionsmentioning
confidence: 99%
“…There is a rich dopaminergic innervation of rat (Awenowicz and Porter, 2002) and primate (Goldman-Rakic et al, 1989) motor cortex and pyramidal tract neurones decrease spontaneous firing with application of dopamine (Awenowicz and Porter, 2002). Furthermore, there is substantial cell loss in the pre-SMA (Camicioli et al, 2007;MacDonald and Halliday, 2002) and caudal intralaminar thalamus (Henderson et al, 2000), and Lewy bodies are present in the cerebral cortex (e.g.…”
Section: Substantia Nigra Echomorphology and Motor Cortex Excitabilitymentioning
confidence: 99%